The relationship between the external environment analysis and banking facilities: An Applied Research in the Rafidain and Rasheed Bank (Journal of Accounting and Financial Studies ( JAFS ), 2017)
Is the subject of environmental analysis of the important issues that should occupy the attention of the departments of banks in general and banks in particular, the research sample, regardless of their size and the nature of its activity, So if the current era and witnessing rapid developments and changes, making the banking environment is more complex and interconnected than ever, And it became not possible for banks to be aware and understand the external environment variables without an analysis of the various constituent elements and influential heavily in its financial and administrative,Therefore research aims to find out the relationship between the external environment and banking facilities analysis application on the Rafidain and Rasheed,The research has come to a number of conclusions Mrs. Mubarak: The most important stages of strategic planning and environmental analysis process, so should the banks interest in this stage and the adoption of objectivity and accuracy in dealing with the environmental information provided by this process in order to face the competition of banks and stay in the labor market,The need to pay banks administrations sample process of environmental analysis of great importance in the next stage to be able to take advantage of what is produced by the external environment of the opportunities and challenges and to reduce the raised and work to get rid of them.